Microwave-assisted hydrodistillation of Aquilaria Subintegra: article - Jamaluddin, Norafiqah; Kadri, Atikah (2017)
Higher demanding of essential oil as pharmaceutical, aromatherapy aid and cosmetics ingredients give large opportunities for global marketing. The international market for essential oil growth rapidly. Thus, it is necessary to find the most suitable method to enhance the quality of essential oil. Conventional method that usually to obtain essential oil have several disadvantages such as longer extraction time, have low extraction yields, laborious and higher operational costing. Presently, alternative extraction method which is able to overcome disadvantages like mentioned above by using microwave-assisted hyrodistillation(MAHD) method. Hence, conventional hydrodistillation (HD) and microwave-assisted hydrodistillation (MAHD) methods has been compared to evaluate their efficiency in terms of yield of extraction of Aquilaria Sub-integra grounded chips and for MAHD only, to investigate effect the power of microwave on the yield of essential oil. The MAHD offers several benefits compared to HD which are shorter extraction time, better yields, and provides a more valuable essential oil from agarwood grounded chips. The experimental results shows the operation time for MAHD was shorter than HD and higher yield results from higher extraction rates by microwave.